ANALISIS KEMAMPUAN MENGOPERASIKAN KOMPUTER DAN SOFTWARE APLIKASI DALAM PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI OLEH GURU DALAM PEMBELAJARAN BIOLOGI DI SMA NEGERI SEKOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the ability to operate computers and application software in the use of information and communication technology by biology teachers at Pekanbaru Public High School. This type of research is descriptive research. The location of the research was carried out in Public High School throughout Pekanbaru City for the 2020/2021 academic year. Research was carried out on January - March 2021. The population in this study were biology teachers who took part in the MGMP totaling 108 teachers at Public High School in Pekanbaru City. The sampling technique used was purposive sampling technique. The sample in this study was 43 biology teachers from Public High School in Pekanbaru City who were registered as active members of the MGMP. Collecting data in this study using a closed questionnaire and analyzed using a Likert scale. Data analysis techniques include validity testing using the SPSS version 25 computer program in 2021, reliability testing and descriptive data analysis. The results showed that the ability to operate computers by teachers in biology learning at SMA Negeri in Pekanbaru city showed 89% results in the (Good) category and the skills to operate application software showed 84.28% results in the (Good) category. These results indicate that the use of Information and Communication Technology by teachers in learning biology at Public High School in Pekanbaru city obtains good results.Key Words: Biology, ICT, Teacher, Utilization